Septic Pulmonary Embolism in a Patient with Generalized Salmonellosis: a Clinical Case and Meta-Analysis - A. D. Strutynskaya; M. A. Karnaushkina; I. E. Tyurin; M. P. Suvorova; S. V. Yakovlev (Антибиотики и Химиотерапия)
Nontyphoid Salmonella are gram-negative bacteria that induce Th1-mediated immunity. They rarely lead to a generalized infection, primarily developing in immunocompromised patients with cellular immunity defects. Septic pulmonary embolism is also a rare condition in which emboli contain microorganisms from extrapulmonary infective foci. The article presents a rare clinical case of a patient with pulmonary embolism and generalized nontyphoid salmonellosis due to the presence of Asp299Gly and Thr399Ile genetic polymorphisms in the TLR4 gene. Such a defect of cell-mediated immunity was a trigger for destructive changes in the lung parenchyma, prothrombotic state, and generalization of the infectious process.